Handbook of research on machine learning foundations and applications (Apple Academic Press, 2022)
"With over 250 figures, tables, and charts, this volume takes the reader on a technological voyage of machine learning (ML) advancements, highlighting the systematic changes in algorithms, challenges, and constraints. The technological advancements in the ML arena have transformed and revolutionized several fields, including transportation, agriculture, finance, weather monitoring, and others. This book brings together researchers, authors, industrialists, and academicians to cover a vast selection of topics in ML, starting with the rudiments of machine learning approaches and going on to specific applications in healthcare and industrial automation. The first section the Handbook of Research on Machine Learning: Foundations and Applications provides an overview of the ethics, security and privacy issues, future directions, and challenges in machine learning.